Oxidative stability of edible plants oils - Madhujith, T.; Sivakanthan, S. (Springer Nature., 2019)
Edible plant oils play a vital role in daily diets of people worldwide. Stability against oxidation is the major factor limiting the application of most edible plant oils for cooking and processing. Most native plant oils vary greatly in their stability to oxidation depending on their composition. Oxidative stability of edible plant oils has been extensively studied to find out the ways of improving their stability against oxidation to widen their application. Synthetic antioxidants are effective to improve the oxidative stability of these oils, however, recently, following the evidences on possible toxicities of synthetic antioxidants, the use of natural plant sources as antioxidant is gaining interest. In addition, modification of composition of the oils through genetic modification is another successful means to improve the oxidative stability of these oils. This chapter focuses on the mechanism and factors of oxidation and ways of improving oxidative stability of oils.
Keywords: Antioxidants; Autoxidation; Hydroperoxides; Photooxidation; Radicals; Refining